Intersectionality in human capital development of indigenous women in Dhaka: mapping the journey in education, employment, and choice of partner - Khaing, Myat Moe (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Development Studies, 2023.